THE DEVELOPMENT OF SENTIMENT ANALYSIS APPROACH FOR IDENTIFYING CUSTOMER INTEREST IN LEATHER BAG - Eka Legya Frannita; Anwar Hidayat; Wawan Budi Setyawan (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2024)
Analyzing user interest has become one of the most popular research topics since identifying the user satisfaction played the essential role to prevent the company profit. This research work aimed to apply sentiment analysis approach for identifying the user interest in leather bag. This research was extremely beneficial to determine the satisfaction of leather bag customers. This research work was done by employing four stages. In the first process, we conducted brainstorming process for determining the exclusion and inclusion of research. In the next process, we collected the data by conducting crawling process from social media review. After collecting the data, we conducted data analysis process by labelling each review into three labels, which were positive sentiment, neutral sentiment and negative sentiment. In the last process, we visualized the result and we summarized the result. The visualization process illustrated that positive sentiment achieved percentage of 28%, neutral sentiment achieved percentage of 69% and negative sentiment achieved percentage of 3%. This result indicates that markets are neutral or not interest enough in leather bag. The analysis process also concluded that News obtained the highest total mentions indicating that Batik is not regularly mention in popular social media. According to those results, innovation or creativity about Batik is should be regularly generated in order to increase the market interest.